Thermal conditions and kinematics associated with final emplacement of the Lyngen nappe - Klæbo, Erik Vågå (UiT Norges arktiske universitet, 2017)
The tectonic boundary of between the Lyngen magmatic complex and the underlaying Nordmannvik have been examined for kinematic indicators. This boundary is characterised by an amphibole facies garnet-mica-kyanite gneiss overlain by a greenschist facies amphibolite/meta-gabbro succession separated by heavily foliated and lineated garnet-mica schist, phyllites and quartzites. Two main populations of lineation were identified: A West verging and a NW verging. Field observations and thin section analyses indicate an overall top to the WNW sense of shear. Not all kinematic indicators show emplacement in this direction; a cluster of indicators located in a synform NE of Nordkjosbotn showed a consistently top to the SE sense of shear. Top to the WNW kinematic indicators were also found on the East side of Storfjorden, 8 km to the east of the Lyngen nappe/Nordmannvik boundary. The emplacement is interpreted to have happened in greenschist facies conditions based on the presence of chlorite in schist and phyllites. Quartz CPO indicate that the temperatures were high enough that rhomb and prism a-slip was dominant with grain boundary migration as the dominant recrystallization mechanism. A top WNW sense of shear indicate that the Lyngen nappe could have been displaced due to extensional collapse or possibly extrusion wedging.